2015
DOI: 10.1136/bmjquality.u208552.w3411
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a community respiratory physiotherapy service for children with severe neurodisability

Abstract: Children with severe disability often have difficulties with secretion clearance leading to recurrent lower respiratory tract infections and prolonged hospital admissions. A community respiratory physiotherapy service was developed for this client group, including a rapid response for acute respiratory illness, and an evaluation was undertaken, comparing admissions and bed-days in hospital for respiratory tract infections, emergency admissions to hospital for any cause, and admission costs for each child for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…This is, for instance, also illustrated in a recent study where a community respiratory physiotherapy service was installed for children with disabilities with an acute infection. This resulted in a reduction of hospital admissions and bed days for these children . A relatively new device, the Free‐Aspire (Medical Products Research, Srl, Legnano, Italy) is an electro‐medical machine for removing secretions.…”
Section: Recurrent Aspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, for instance, also illustrated in a recent study where a community respiratory physiotherapy service was installed for children with disabilities with an acute infection. This resulted in a reduction of hospital admissions and bed days for these children . A relatively new device, the Free‐Aspire (Medical Products Research, Srl, Legnano, Italy) is an electro‐medical machine for removing secretions.…”
Section: Recurrent Aspirationmentioning
confidence: 99%
“…This resulted in a reduction of hospital admissions and bed days for these children. 35 A relatively new device, the Free-Aspire (Medical Products Research, Srl, Legnano, Italy) is an electro-medical machine for removing secretions. The device utilizes Vak} um technology: during expiration the airflow is accelerated by the Venturi effect inside a special connector.…”
Section: Gastro-oesophageal Refluxmentioning
confidence: 99%
“…As shown in the present study, these represented a significant part of morbidities requiring pediatric intensive unit care. Considering primary preventive measures such as passive and active immunization and respiratory physiotherapy, secondary protection such as antibiotherapy and bronchodilator therapy and tertiary prophylaxis such as respiratory physiotherapy may reduce pediatric intensive care unit admissions of patients with chronic neurological diseases (5)(6)(7) .…”
Section: Dıscussıonmentioning
confidence: 99%
“…It has been demonstrated that specialist respiratory physiotherapy treatment can be highly effective in the acute and long-term management of CYP with complex disabilities and recurrent or persistent respiratory illness 8 9 and offering these services within the community improves patient experience by keeping CYP closer to home and with their families. 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…An early service evaluation in 2015 identified the CCRPS to be effective in reducing ED attendances, hospital admissions and length of stay for respiratory tract infections. 10 We now report the results of a further service evaluation which was conducted from 1 April 2019 until end of March 2020 to look at admissions prevented and user satisfaction with the service.…”
Section: Introductionmentioning
confidence: 99%